Morphological Errors Found in Indonesian Students’ English Compositions of Application Letter - Elwa Junaidi; M. Zaim (Universitas Negeri Padang, 2022)
A number of morphological errrors can be found in students’ English compositions of application letter. The errors were possibly caused by a lack of students understanding about the rules in morphology.The purposes of this research were to explain the (1) morphological errors, (2) the frequencies of morphological errors, and (3) the sources of errors in students’ English compositions of application letter. The research applied a descriptive method. The data from students’ compositions of application were collected by using documentation technique. The research results indicated that there were two categories of morphological error, specifically noun morphological errors (indicated by the problems with noun plural –s) and verb morphological errors indicated by the problems with present third person singular –s). The most common errors were noun morphological errors. Furthermore, there are two sources of errors found in the application letters of students. They were interlingual errors (transfer of morphological elements) and intralingual & development errors. (overgeneralization & ignorance of rule restriction).